Public perception of transportation systems in the halal logistics - Ingsih, Ita Suhermin; Rahmawati, Anita (Fakultas Teknik UB, 2020)
The current government, Government Business Entities and mass media in Indonesia are starting to pay attention to halal, because the turnover of halal products worldwide has reached nearly 2 trillion dollars while Indonesia is still more likely to be a consumer than a producer. Not only food, consumers in the world today want cosmetics for pharmaceutical products that have been halal-certified. In Indonesia, problems with the halal market potential are currently still affected by discourse. Indonesia's awareness is still limited, it has not dared to act, whereas in non-Muslim countries themselves many implement halal supply chains. The establishment of the Halal Hub Port in Tanjung Priok as the first Halal Hub Port pilot project in Indonesia was the forerunner to the establishment of the Halal Hub Port in other parts of Indonesia. In addition to the availability of halal logistical infrastructure, it is also necessary to pay close attention to the needs of halal logistic transportation needs. This research was conducted on 89 respondents who are academics of the Islamic University of Malang. By using the Descriptive Analysis method, it will be known which of the variables that most influence the discourse of the halal transportation / cargo system in Indonesia. The results of the study showed that more than 90% of respondents considered important variables needed in the implementation of halal logistics, namely sorting goods according to types as well as halal and non-halal, separating halal and non-halal products, setting the position of goods in cargo, using vehicles specifically for halal products, maintenance of cargo cleanliness, training of halal logistic officers, and health care for halal logistic officers. In addition, the use of halal logistic stickers can also provide halal logistic warranty from producers to consumers.